Evaluating the impact of maternal vitamin D supplementation on sow performance: II. Subsequent growth performance and carcass characteristics of growing pigs - Flohr, Joshua R.; Woodworth, Jason C.; Bergstrom, J. R.; Tokach, Michael D.; Dritz, Steven S.; Goodband, Robert D.; DeRouchey, Joel M. (My University, 2017)
A of subsample of 448 growing pigs (PIC 327 x 1050) weaned from 52 sows fed varying dietary vitamin D regimens were used in a split-plot design to determine the effects of maternal and nursery dietary vitamin D on growth performance. Sows were previously administered diets containing vitamin D as vitamin D-3 (800, 2,000, or 9,600 IU/kg) or as 25(OH) D3 (50 mu g [or 2,000 IU vitamin D equivalent]/kg from HyD; DSM Nutritional Products, Parsippany, NJ). Once weaned, pigs were allotted to pens on the basis of previous maternal vitamin D treatment, and then pens were randomly assigned to 1 of 2 nursery vitamin D dietary regimens (2,000 IU of vitamin D-3/ kg or 50 mu g 25(OH) D-3/kg). Pigs remained on nursery vitamin D treatments for 35 d, and then they were provided common finishing diets until market (135 kg). Growing pig serum 25(OH)D-3 suggested that maternal dietary vitamin D influenced (P < 0.001 at weaning) serum concentrations early after weaning, but nursery vitamin D regimen had a larger impact (P < 0.001) on d 17 and 35 postweaning. Overall growth performance was not influenced by nursery vitamin D dietary treatments. From d 0 to 35 in the nursery, pigs from sows fed increasing vitamin D3 had increased (quadratic, P < 0.003) ADG and ADFI, but G:F was similar regardless of maternal vitamin D regimen. Also, pigs from sows fed 50 mu g/kg of 25(OH) D-3 had increased (P = 0.002) ADG compared with pigs weaned from sows fed 800 IU of vitamin D3. Throughout finishing (d 35 postweaning until 135 kg), ADG was increased (quadratic, P = 0.005) and G: F was improved (quadratic, P = 0.049) with increasing maternal dietary vitamin D-3. Also, pigs from sows fed 50 mu g/kg of 25(OH)D-3 had increased (P = 0.002) ADG compared with pigs weaned from sows fed 800 IU of vitamin D-3. Carcass data were collected from a subsample population separate from that used for the growth performance portion of the study, and a total of 642 carcasses from progeny of sows fed the varying dietary vitamin D treatments were used. Live BW of pigs at marketing and HCW were heavier (P < 0.030) for pigs from sows previously fed 25(OH)D-3 compared with pigs from sows fed 9,600 IU of vitamin D-3. Overall, pigs from sows fed 2,000 IU of vitamin D-3 grew faster after weaning compared with pigs from sows fed 800 or 9,600 IU of vitamin D-3. Pigs from sows fed 25(OH)D-3 hag greater ADG compared with pigs from sows fed 800 IU of vitamin D-3, and they had increased final BW and HCW compared with pigs from sows fed 9,600 IU of vitamin D-3.
Citation: Flohr, J. R., Woodworth, J. C., Bergstrom, J. R., Tokach, M. D., Dritz, S. S., Goodband, R. D., & DeRouchey, J. M. (2016). Evaluating the impact of maternal vitamin D supplementation on sow performance: II. Subsequent growth performance and carcass characteristics of growing pigs. Journal of Animal Science, 94(11), 4643-4653. doi:10.2527/jas2016-0410
Keywords: 25(Oh)D-3; Finishing Pig; Growth; Nursery Pig; Vitamin D; Skeletal-Muscle Development